Induced mutagenesis breeding through acute and chronic gamma irradiation for yield improvement in two Bambara groundnut [Vigna subterranea (L.) Verdc.] varieties - Muhammad, Isma'ila (2021)
Bambara groundnut [Vigna subterranea (L.) Verdc.] is a highly nutritious underutilized legume with enormous potentials to sustain global food security. However, limitations due to the crop flower's autogamous and small nature had limited its potential for improvement through conventional breeding with a <2% success rate recorded from the previous studies. Thus, the most viable method of improving this crop is by creating genetic variability through induced mutagenesis. This study was conducted to induce genetic variability in two Bambara groundnut varieties (Ex-Sokoto and Karo) through acute and chronic gamma irradiation to developed high-yielding varieties. Healthy seeds were exposed to acute gamma irradiation using Cesium-137 at the doses of 0 (Control), 25, 50, 75, 100, 125, 150, 175, 200, 250, and 300 Gy. For chronic irradiation, two weeks old healthy seedlings were exposed to the accumulated doses of 0 (Control), 8.52 (Ring 2), 17.04 (Ring 3), 35.56 (Ring 4), 34.09 (Ring 5), 42.61 (Ring 6), 59.65 (Ring 7), 93.74 (Ring 8), 144.87 (Ring 9), 255.64 (Ring 11) and 570.94 (Ring 15) Gy respectively for 852:08 hours in Gamma Green House (GGH) at Nuclear Malaysia until physiological maturity. The experiments were laid down in Randomized complete block design (RCBD) with three replications and four treatments for acute gamma irradiation. However, for chronic gamma irradiation, it was (RCBD) with three replications and eleven treatments at field 15 Faculty of Agriculture, Universiti Putra Malaysia. The results for optimum lethal dose (LD) indicated highly significant differences (p ≤ 0.01) for all evaluated traits except for internode length, which did not show any significant difference (p ≤ 0.05). The established lethal doses (LD25%, 50%, 75%) for acute gamma irradiation were 73, 160, 248 Gy and 68, 148, 227 Gy for Ex-Sokoto and Karo varieties. Similarly, for chronic gamma irradiation, the established lethal doses (LD25%, 50%, 75%) were 47, 250, 444 Gy and 70, 264, 452 Gy for Ex-Sokoto and Karo varieties. The frequency of chlorophyll mutants identified includes; albina, chlorina, xantha, viridis, maculata, and virescent. The occurrence of a virescent type of chlorophyll mutants was the highest between the two varieties. In acute, chlorophyll mutants' overall effectiveness and efficiency were 6.43 and 22.06 among EX-Sokoto, while 4.58 and 17.35 were identified among the Karo variety. Similarly, in the chronic phase, chlorophyll mutants' overall effectiveness and efficiency were 12.02 and 11.51 among EX-Sokoto and 12.56 and 12.09 among Karo variety. The most noticeable macro mutants identified in this study were linked to the plant height, flowering and maturity period, pods, leaf, and growth habits. The results from both acute and chronic mutagenesis at M1 to M4 generations display significant improvements among the different mutagens doses used in this study. It was observed that both acute and chronic gamma irradiation stimulates plant growth at low and moderate gamma irradiation doses compared to the higher gamma irradiation doses. Most of these mutants were identified in the acute phase at the range of 68 to 150 Gy and 73 to 160 Gy for Karo and Ex-Sokoto varieties. Therefore 150 Gy and 160 Gy are regarded as appropriate gamma irradiation dose rates that can be used to induce viable mutants in these varieties. Similarly, among the chronic gamma-irradiated mutants, the most outstanding doses include; 42.61 (ring 7), 25.56 (ring 9), 144.87 (ring 4) and 59.56 (ring 6). Significant improvement was achieved in yield and yield components in both acute and chronic gamma irradiation methods. In the acute phase, the highest mean yield recorded was 10.07 (ESK 250-P11) and 11.60 (KRO 70- P16) t ha−1 for EX-Sokoto and Karo varieties. In contrast, 10.37 (ESK R14-P6) and 10.85 (KRO R9-P4) were recorded as the highest mean for EX-Sokoto and Karo variety in the chronic phase. This result is more than two folds of the reported mean yield per hectare in most existing varieties, including the two used in this study. There was high heritability coupled with high genetic advance for most of the studied traits in yield and yield components both in acute and chronic mutagenesis in this study. Therefore, effective selection can be achieved using those traits in subsequent generations. Among acute established mutants, ESK 75-P7 5.11, ESK 75-P15 6.99, ESK 160-P17 7.61, ESK 250-P11 10.07, ESK 250-P7 7.18 and KRO 70-P16 11.60, KRO 70-P5 6.60, KRO 150- P3 11.16, KRO 230-P3 7.68, KRO 230-P3 6.60 were identified as mutants that can be used for further study. For chronic mutants, ESK R6-P9 6.64, ESK R7-P4 6.76, ESK R8- P7 7.47, ESK R11-P5 8.97, ESK R11-P5 6.80, ESK R14-P6 10.37 and KRO R3-P1 6.00, KRO R6-P7 9.44, KRO R7-P3 6.62, KRO R8-P7 7.58, KRO R9-P4 10.85, KRO R11- P9 9.93 can be used. Yield per plant observed a highly significant and positive correlation with most of the rest of the traits studied. In conclusion, this study discovered that induced physical mutagen through acute and chronic gamma radiation effectively induces morphological genetic divergence in Bambara groundnuts and has established the successful approach of induced physical mutagenesis in the two varieties used in this study.